Чотирирівнева архітектура інтернету речей для вітроенергетичних систем: моніторинг, оптимізація та інтеграція з мережею - Сиротюк, Сергій Валерійович; Скляр, Олександр Григорович; Пташник, Вадим Вікторович; Климчук, Владислав Васильович; Валовські, Ґжегож; Syrotyuk, Serhiy; Skliar, Oleksandr; Ptashnyk, Vadym; Klymchuk, Vladyslav; Wałowski, Grzegorz (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті розглянуто, що таке Інтернет речей, як функціонують вітрові електростанції та чому доцільно інтегрувати IoT із відновлюваною енергетикою. Висвітлено моніторинг робочих параметрів вітрових турбін, автоматизацію й оптимізацію процесів, а також прогнозування відмов і предиктивне технічне обслуговування. Наведено приклади систем вітрових електростанцій, у яких використовується Інтернет речей, а також технології та платформи, що застосовуються для моніторингу. На основі визначення викликів і обмежень, пов’язаних з управлінням даними, окреслено перспективи розвитку Інтернету речей у вітроенергетиці. /// EN: The article examines the role of the Internet of Things (IoT) in modern wind energy systems and substantiates the feasibility of integrating IoT technologies with wind power generation. A unified four-level architecture for IoToriented wind energy systems is proposed, structured according to the increasing complexity of control, decisionmaking time horizons, and the scale of integration with the physical power system. The first level covers real-time monitoring and control based on sensor data. The second level involves adaptive and predictive control supported by machine learning for failure prediction and condition-based maintenance. The third level focuses on wind-farmlevel optimization through digital twins, cloud analytics, and coordinated maintenance planning. The fourth level addresses lifecycle-oriented management, cyber-physical security, grid interaction, and environmental analytics. The article also reviews industrial implementations of IoT in wind energy, including monitoring and diagnostic platforms and AI-based decision support tools. Particular attention is paid to SCADA integration, digital twins, and secure data exchange mechanisms. The main technical, organizational, and economic challenges of large-scale IoT deployment are outlined, including sensor reliability, communication constraints, cybersecurity risks, data quality, and scalability of intelligent analytics. It is concluded that IoT technologies are a key enabler for improving the efficiency, reliability, and long-term sustainability of wind energy infrastructure.
Four-level internet of things architecture for wind energy systems: monitoring, optimization, and grid integration
Keywords: IoT; відновлювана енергетика; турбіна; вітрові електростанції; штучний інтелект; офшорна енергетика; renewable energy; turbine; wind farms; AI; offshore